Frequency of Human Immunodeficiency Virus, Hepatitis B, and Hepatitis C Among Antenatal Women at a Tertiary Care Hospital: HIV, HBV, and HCV Prevalence in Antenatal Women - Mallick, Rumsha; Baloch, Falak Naz; Rashed, Faryal; Nazir, Namia; Ismail, Atruba; Maryam, Hafiza (Pakistan Journal of Health Sciences, 2026)
Human Immunodeficiency Virus (HIV), Hepatitis B (HBV), and Hepatitis C (HCV) are major blood-borne infections. In Pakistan, the prevalence of HCV is predicted to range from 8% to 15%, while the combined frequency of HBV and HCV affects 7.6% of the population. Prenatal HIV screening is recommended to prevent mother-to-child transmission. Objectives: This study aimed to determine the frequency of HIV, HBV, and HCV among antenatal patients at a tertiary healthcare facility. Methods: A descriptive cross-sectional study was carried out at the Civil Hospital Karachi Obstetrics and Gynecology unit 3 over 6 months, from October 7, 2022, to April 8, 2023. Pregnant women aged between 15-49 years, with a gestational age >20 weeks, presenting for routine antenatal care were enrolled using non probability consecutive sampling. All participants were screened for HIV, HBV, and HCV. Data were analyzed using SPSS version 25.0. Results: Among 187 women, the mean age was 32.29 ± 3.91 years, and the mean gestational age was 22.87 ± 1.34 weeks. The prevalence rates of HIV, HBV, and HCV were 13 (7%), 23 (12.3%), and 43 (23%), respectively. Conclusions: Among antenatal patients, the prevalence of HIV, HBV, and HCV was 13 (7%), 23 (12.3%), and 43 (23%), respectively. This underscores the need for regular screening during pregnancy. Regular screening during pregnancy is mandatory to prevent these infections from being transferred from the mother to the child.